Spiritual Healing dalam Tradisi Sufi - Jarman Arroisi (TSAQAFAH, 2018)
In this modern era, some people are more often faced with the high social, economic, political, legal problems. As a result, difficult, anxious, and depression continue to overshadow, even inevitable sekes again. Various ways taken to reduce the burden, to healt of life. There are sports, yoga, going to clinic, alternative medicine, and others including counseling to a psychologist. Psychologists receive an order surge over this problem. But as its limitations, the problem never finished, even more so. This study is present to find out the failure of psychologists to solve problems and to find alternative solutions as models. The construction begins from a critical analytical to the human concept that psychologists believe. Then proceed by analyzing the pattern of overcoming the problem. On the basis of in-depth study, found that the psychologist's inability is not due to his method, but rather his concept of an incomplete human being. According to him humans have two dimensions jismiyah and nafsiyah, without belief aspects of ruhiyah as its essence. This concepts have implications for counseling that do not touch the essence of the real problem. The psychologist's point of view about human beings, and the pattern of unraveling such problems are different from those of the Sufis. To heal the mental healt, most of Sufis such as Robi'ah al-Adawiyah, Abi Yazid al-Bistami, al-Hallaj and al-Qushyairi prefer the spiritual approach as the therapist. With a spiritual approach, the core content untouched by psychologists has become the right momentum momentum. They can not only finish their souls, but more of that the benefits, even the tranquility and happiness of life.